Some theoretical aspects of the vocational choice - POCIŪTĖ, P. (Psichologija, 1997)
Professional interest in the process of how an individual selects an occupation is relatively new in Lithuania. The ever-increasing range of occupational alternatives and the accompanying uncertainties and confusion have created the need for professional assistance in selecting a career. The way in which assistance is provided will be influenced by the way which the assistant views the process. The goal in this article is to briefly survey Super’s developmental self-concept theory of vocational behaviour and social learning approach to career decision-making - Krumboltz theory.